Distribucion de las poblaciones del acaro rojo Panonycchus citri Mc Gregor en agrios - Mico, V.=700 1 Laborda, R.; Garcia-Mari, F.; Soto, T.; Costa-Comelles, J.
En, Es)
ilus., 5 ref.
Keywords: ACARINA; DISTRIBUCION GEOGRAFICA; FRUTAS CITRICAS; PANONYCHUS CITRI; MUESTREO; ESPAÑA; DISPERSION; ACARO ROJO; CORRELACION; AGRIOS